Validation of the H-512 double-cross coro (Zea mayz L.) hybrid in the state of Veracruz-México. - Tosquy, Oscar (2016)
The outstanding results of the corn research program, with respect to the production of more efficient genotypes in the use of the available resources, as well as the development of the technology needed for its application, call for the establishment of semi-commercial plots, where such results can be tried and its kindness verified under the climate, soil and the farmers' management. The objective of this trial was to validate and show the performance of the H-512 corn hybrid on the tropical region of the State of Veracruz. Validation plots were established during the Spring-summer of 1992 at the localities of Cotaxtla, Acayucan, San Andres Tuxtla and Papantla, Yeracruz. The H-512, HCSV-23, D-471 x TTC-63, D-471 x ST- 549 and the controls VS-536, 8-830 and C-343 genotypes were included. The plots’ area was 2 hectares each, thus every genotype was planted on 0.25 ha and the cultural practices applied were the ones suggested for each zone. The H-512 hybrid registered the highest yields in Cotaxtla and Acayucan with 7605 and 6438 kg/ha, respectively. This hybrid was surpassed by the simple-cross experimental hybrid HCSV-23 in San Andres Tuxtla and Soledad de Doblado. As an average of the five localities, the H-512 showed the highest yields and registered an intermediate plant height, good husk cover, good plant and ear health and lodging resistant. It can be concluded that the H-512 hybrid adapts well to the tropical zones of Veracruz.